2012
DOI: 10.1007/978-3-642-33863-2_52
|View full text |Cite
|
Sign up to set email alerts
|

Fun with Asynchronous Vision Sensors and Processing

Abstract: Abstract. This paper provides a personal perspective on our group's efforts in building event-based vision sensors, algorithms, and applications over the period [2002][2003][2004][2005][2006][2007][2008][2009][2010][2011][2012]. Some recent advances from other groups are also briefly described.When Mahowald and Mead built the first silicon retina with asynchronous digital output around 1992 [1], conventional CMOS active pixel sensors (APS) were still research chips. It required the investment by industry of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Readers are referred to the source code for implementation details. DS was inspired by the organization of V1 direction selective simple cells (Delbruck, 2008 , 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Readers are referred to the source code for implementation details. DS was inspired by the organization of V1 direction selective simple cells (Delbruck, 2008 , 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…The DVS event camera [2] had its genesis in a frame-based silicon retina design where the continuous-time photoreceptor was capacitively coupled to a readout circuit that was reset each time the pixel was sampled [44]. More recent event camera technology has been reviewed in the electronics and neuroscience literature [10], [36], [38], [45], [46], [47]. Although surprisingly many applications can be solved by only processing DVS events (i.e., brightness changes), it became clear that some also require some form of static output (i.e., "absolute" brightness).…”
Section: Event Camera Designsmentioning
confidence: 99%
“…For example, in an assisted living scenario a bank of such sensors can successfully be utilized to detect and classify fast vertical motions as unintended occasional falls, indicative of an preemptive alarm situation [Fu et al, 2008]. Tracking scenarios have been investigated to steer real-world interaction [Delbrück, 2012] as well as in microbiology set-ups [Drazen et al, 2011]. Basic research investigations have been reported as well.…”
Section: Previous Workmentioning
confidence: 99%